An Empirical Investigation of Architectural Heritage Management-Implications for Tourism: The Case of Portugal - Gholitabar, Shahrbanoo (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Heritage is treated as cultural part of a society’s tradition since it transmits the value of the past as history. Additionally, it is viewed a substantial asset of the cities and urban areas with potential for infrastructural enhancement, improvement of image, and highly utilized as economic resource for urban tourism. Cultural heritage has attracted the attention of tourism planners, urban planners, and historians as means to restructuring human habitat in terms of material and non-material heritage encompassing architecture, monuments, historical relics, artefacts, artistic icons, celebrations, and folklore. Now-a-days, historical buildings as part of cultural heritage, have become a significant tourism resource; therefore, numerous destinations have funded and supported their renovation and reuse. Such change in attitudes towards heritage restoration resulted in heightened awareness at state and European Community levels of the economic. Employing potential of the heritage for tourism purposes has contributed to this. The aim of this study is manifold. First, to investigate and reveal the potentials of architectural heritage in the context of tourism destination development, as well as, examination of public sector policies and plans toward the conservation and preservation of these resources. Secondly, to appraise the outcome of preservation and its implication for tourism. The study is an effort to explore and figure the outcome of interrelationships between tourism and architectural heritage sites through tourists’ image and perception. Study assumes that such multidimensional process and analysis will achieve a pathway towards the protection and reutilisation of heritage sites with positive implications for tourism sector. For the purpose of this research, numerous heritage sites are sampled in Portugal as study landscape. A mixed research method has been utilized to gauge tourists’ image/perception of heritage resources, reuse and impact (i.e., quantitative approach). A qualitative approach utilized to assess the priority of tourists in their visiting and the public-sector policies towardheritage resource management and planning. And Fuzzy logic method to assess the architectural value, tourism and preservation potential of historical buildings in Porto/ Aveiro. The contribution and implications of the study is also elaborated. The result revealed that architectural heritage resource is the main resource of appealing tourists. Also, the study to date demonstrate architectural value, tourism and preservation potential of observed buildings by evaluation through fuzzy logic methods.

ÖZ: Tarihi ve kültürel miras toplum geleneğinin kültürel bir parçası olup geçmişte yaşanan olayların değerini tarihi olarak değerlendirip aktarılmasıdır. Ayrıca, buna ek olarak, altyapı geliştirme, imajın iyileştirilmesi ve kent turizmi için ekonomik kaynak olarak yüksek oranlarda kullanılabilen kentlerin ve kentsel alanların önemli bir varlığı olarak görülmektedir. Kültürel miras, turizm planlamacılarının, kent planlamacılarının ve tarihçilerin ilgisini, mimari, anıtlar, tarihi eserler, sanatsal ikonlar, kutlamalar ve folkloru kapsayan maddi ve manevi miras açısından insan yaşam alanını yeniden yapılandırmaya yönelik araçlar olarak karşımıza çıkmaktadır. Kültürel mirasın parçası olan tarihi binalar önemli bir turizm kaynağı haline gelmiştir. Bu nedenle, çok sayıda yerin, yenileme, restorasyon ve yeniden kullanımı finanse edilmiş ve desteklenmiştir. Kültürel ve tarihi miras restorasyonuna yönelik tutumlardaki bu tür değişiklikler, devlette ve Avrupa Topluluğunda ekonomik düzeyde yüksek farkındalığa neden olmuştur. Tarihi ve Kültürel Mirasın turizm amaçlı potansiyelinin kullanılması da buna katkıda bulunmuştur. Bu çalışmanın amacı çok yönlüdür. Birincisi, mimari mirasın turizm bölgesi gelişimi bağlamındaki potansiyellerini araştırmak ve ortaya çıkarmak ve kamu kaynaklı politikaların incelenmesi, kaynakların korunması ve buna yönelik planlar. İkincisi, korunmanın sonucunu ve bunun turizm açısından önemini değerlendirmektir. Çalışma turistlerin imaj ve algıları ile turizm ve mimari miras alanları arasındaki karşılıklı ilişkilerin sonucunu keşfetmek ve bunları bulmak içindir. Ayrıca, bu araştırma çok boyutlu süreç ve analizin, turizm sektörü için olumlu etkileri olan miras alanlarının korunması ve yeniden kullanılmasına yönelik bir yol bulacağını varsayıyor. Bu araştırmada, Portekiz'de çalışma arazisi olarak sayısız miras alanı örneklenmiştir. Turistlerin miras kaynakları, yeniden kullanımı ve etkisi hakkındaki imaj / algılamalarını (ör. Nicel yaklaşım) ölçmek için karışık bir araştırma yöntemi kullanılmıştır. Ziyaret eden turistlerin önceliğini ve miras kaynakları yönetimi ve planlamasına yönelik kamu sektörü politikalarını değerlendirmek için niteliksel bir yaklaşım kullanılmıştır. Porto / Aveiro'daki tarihi binaların mimari değerini, turizmi ve korunma potansiyelini değerlendirmek için bulanık mantık metodu kullanılmıştır. Bu çalışmanın katkısı ve sonuçları şu şekilde gelişmiştir. Mimari miras kaynağının turistler için çekiciliğinin ana kaynağı olduğunu ortaya koydu. Ayrıca, yapılan çalışmada gözlenen binaların bulanık mantık yöntemiyle değerlendirilerek mimari değerini, turizm ve koruma potansiyelini ortaya koymaktadır.
Doctor of Philosophy in Tourism Management. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Tourism, 2018. Co-Supervisor: Prof. Dr. Carlos Manuel Martins da Costa and Supervisor: Prof. Dr. Habib Alipour.
Keywords: Tourism; Historic buildings--Conservation and restoration--Tourism--Portugal; Architectural Heritage--Tourism--Portugal; Heritage preservation and reuse; architectural heritage resources; heritage resource planning and management; tourism; case of Portugal